ARF: a versatile DNA damage response ally at the crossroads of development and tumorigenesis - Kotsinas, Athanassios; Papanagnou, Panagiota; Evangelou, Konstantinos; Trigas, George C.; Kostourou, Vassiliki; Townsend, Paul; Gorgoulis, Vassilis G. (Frontiers in Genetics, 2014)
ARF is a tumor suppressor protein that senses oncogenic and other stressogenic signals. It can trigger p53-dependent and -independent responses with cell cycle arrest and apoptosis induction being the most prominent ones. Other ARF activities, particularly p53-independent ones, that could help in understanding cancer development and provide potential therapeutic exploitation are underrated. Although ARF is generally not expressed in normal tissues, it is essential for ocular and male germ cells development. The underlying mechanism(s) in these processes, while not clearly defined, point towards a functional link between ARF, DNA damage and angiogenesis. Based on a recent study from our group demonstrating a functional interplay between ATM and ARF during carcinogenesis, we discuss the role of ARF at the crossroads of cancer and developmental processes.